Finanza, finanziarizzazione, neoliberismo - Angelo Salento (Quaderni di Sociologia)
This article discusses the relationship between neoliberalism and financialization. It is widely recognized that financial accumulation plays a central role in the neoliberal era, both because neoliberalism is fundamentally supported by financial actors and because its epistemology has operated as a lever for the expansion of financial transactions and the power of financial actors. However, the boundary between the two constructs remains uncertain, also because the expansion of financial accumulation is not exclusive to the neoliberal era. Therefore, in this contribution, after identifying the essential features of financialization processes described by the classics of social sciences, it is argued that what distinctively characterizes financialization in the neoliberal era are two interconnected aspects: the pervasive influence of finance and financial calculation on economic governance (particularly the codification of shareholder value maximization as the keystone of corporate control, i.e., as the primary goal of companies’ economic actions) and the impact of contemporary financialization on the dynamics of social reproduction through a process of financialization of the foundational economy.